2010
DOI: 10.5194/acp-10-5707-2010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen (H<sub>2</sub>) emissions and their isotopic signatures (H/D) from a motor vehicle: implications on atmospheric H<sub>2</sub>

Abstract: Abstract. Molecular hydrogen (H 2 ), its isotopic signature (deuterium/hydrogen, δD), carbon monoxide (CO), and other compounds were studied in the exhaust of a passenger car engine fuelled with gasoline or methane and run under variable air-fuel ratios and operating modes. H 2 and CO concentrations were largely reduced downstream of the three-way catalytic converter (TWC) compared to levels upstream, and showed a strong dependence on the air-fuel ratio (expressed as lambda, λ). The isotopic composition of H 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…At the bottom of the table are estimates by different authors of the global average χ (H 2 ) and δD(H 2 ). Vollmer et al (2010) indicate that this source signature may be lower for modern cars and certain driving conditions. Results from a polluted station in the Netherlands also indicate this .…”
Section: Stable Isotope Studies Of Hmentioning
confidence: 96%
See 1 more Smart Citation
“…At the bottom of the table are estimates by different authors of the global average χ (H 2 ) and δD(H 2 ). Vollmer et al (2010) indicate that this source signature may be lower for modern cars and certain driving conditions. Results from a polluted station in the Netherlands also indicate this .…”
Section: Stable Isotope Studies Of Hmentioning
confidence: 96%
“…Recently, isotope effects in the production processes of H 2 have been studied (Gerst and Quay, 2001;Rahn et al, 2002bRahn et al, , 2003Röckmann et al, 2003;Rhee et al, 2006a;Feilberg et al, 2007;Rhee et al, 2008;Röckmann et al, 2010a,b;Vollmer et al, 2010;Walter et al, 2011;Haumann et al, 2012), as well as the isotope effects in the H 2 uptake by soils (Gerst and Quay, 2001;Rahn et al, 2002a;Rice et al, 2011). Two chemical transport models have been adapted to incorporate the stable isotopic composition of H 2 , namely GEOS-CHEM (Price et al, 2007) and TM5 (Pieterse et al, 2009(Pieterse et al, , 2012, and many more δD data have become available for the validation of such models (Rice et al, 2010;Batenburg et al, 2011).…”
Section: Stable Isotope Studies Of Hmentioning
confidence: 99%
“…Tropospheric H 2 is enriched in deuterium with δD ∼ +130 ‰, (Gerst and Quay, 2001;Rhee et al, 2006;Rice et al, 2010;Batenburg et al, 2011) compared to surface emissions from fossil fuel combustion and biomass burning (δD approximately −200 ‰ and −300 ‰, respectively) (Gerst and Quay, 2001;Rahn et al, 2002;Röckmann et al, 2010a;Vollmer et al, 2010). As originally proposed by Gerst and Quay (2001) from budget closure, the photochemical sources of H 2 are also enriched in deuterium with δD between ∼ +100 ‰ and +200 ‰, (Rahn et al, 2003;Röckmann et al, 2003Röckmann et al, , 2010bFeilberg et al, 2007;Nilsson et al, 2007Nilsson et al, , 2010Pieterse et al, 2009 (Novelli et al, 1999;Hauglustaine and Ehhalt, 2002;Ehhalt and Rohrer, 2009;Pieterse et al, 2011) the extreme deuterium depletion relative to ambient atmospheric H 2 makes it a quite important contributor to the isotope budget (Price et al 2007;Pieterse et al 2011).…”
Section: Abstract Biologically Produced Molecular Hydrogen (H 2 )mentioning
confidence: 99%
“…Our results are (as expected from the uncorrected results) larger than these other estimates. Vollmer et al (2010) studied emissions from a passenger car engine, and showed that the absolute quantities of H 2 and CO emitted, and the H 2 /CO ratio depend on the operational regime. They found that exhaust H 2 concentrations (after catalyst) decrease below the atmospheric H 2 concentrations in fuel lean functioning conditions; if this is the general rule, then fluent traffic should not have a large impact on the atmospheric H 2 mole fractions (while still affecting atmospheric CO).…”
Section: H 2 /Co Ratios From Traffic Emissionsmentioning
confidence: 99%